Enhancing customer satisfaction towards the service quality of Soekarno-Hatta International Airport using servqual and binary logistic regression - Graciela, Felice; Satitidjati Dewayana, Triwulandari; Habyba, Anik Nur (OPSI, 2024)
The world is experiencing rapid change, leading to transformations in human lifestyles that necessitate adaptation. However, the aviation industry appears to have reached a point of stagnation. Soekarno-Hatta International Airport must adapt to the new needs and demands of passengers by implementing necessary changes and incorporating the latest available technologies. To gain a deeper understanding of passenger satisfaction regarding the service quality at Soekarno-Hatta International Airport, the SERVQUAL method and Binary Logistic Regression Analysis will be employed. Both methods aim to identify services that has significant impact and determine the relative influence of these services on the overall service quality at Soekarno-Hatta International Airport. The results of the SERVQUAL method in this study indicate that there are 14 services at Soekarno-Hatta International Airport that do not meet passenger satisfaction standards, with a need for particular attention to the reliability dimension. Subsequently, the Binary Logistic Regression analysis results indicate that only parking price and ambiance significantly influence passenger satisfaction, with the likelihood of increasing satisfaction being 1.7732783 and 2.0773711 times respectively. Focus should be placed on improving operational accuracy through stringent Standard Operating Procedures (SOPs) and comprehensive staff training, reducing supplementary expenses like toll charges, expanding parking facilities, and optimizing parking flow, improving illumination, customer engagement, and noise control measures.